C1q and immunoglobulins mediate activity-dependent synapse loss in the adult brain - Gerard Crowley; Minjung Kim; Nathanael O’Neill; Emir Turkes; Fateme Ghasemi; Luca Giudice; Sebastiaan De Schepper; Benjy J. Y. Tan; Benito Maffei; Laís S. S. Ferreira; Julie Rebejac; Javier Rueda-Carrasco; et al. (Science, 2026)
Complement component 1q (C1q), the initiator of the classical complement cascade, mediates synaptic elimination in development and disease, yet the triggers for its deposition on synapses remain unclear. Using in vivo chemogenetics, we demonstrate that neuronal hyperactivity induces region-specific, C1q-dependent synapse loss in the adult hippocampus. Suppressing perforant pathway hyperactivity in a mouse model of Alzheimer’s disease reduced local amyloid-β amounts and C1q deposition and partially rescued synapse loss. Combining spatial transcriptomics, live cell tracking, and super-resolution microscopy, we identified association of antibody-secreting B-lineage cells in the adult hippocampus with activity-dependent, C1q-mediated synapse loss under physiological conditions. Together, these findings link neuronal hyperactivity to C1q-mediated synapse loss in the adult brain and implicate immunoglobulins as players in this process.